Suppression of mold-metal reactions during investment casting - Idris, Mohd. Hasbullah; Ourdjini, Ali; Hamzah, Esah; Clegg, Allen (Wiley InterScience Publisher, 2000)
The paper explains the problems associated with the investment casting of magnesium alloys, the options for overcoming these problems, and the preliminary results of a research programme to establish an investment casting process that is suitable for the processing of magnesium alloys. In particular, the paper reports on the suitability of alternative mold materials and the use of inhibitors to suppress reactions between the mold and alloy.